Charge transfer in dissociating iodomethane and fluoromethane molecules ionized by intense femtosecond X-ray pulses - Boll, Rebecca; Erk, Benjamin; Coffee, Ryan; Trippel, Sebastian; Kierspel, Thomas; Bomme, Cédric; Bozek, John D.; Burkett, Mitchell; Carron, Sebastian; Ferguson, Ken R.; Foucar, Lutz; Küpper, Jochen; et al. (My University, 2016)
Ultrafast electron transfer in dissociating iodomethane and fluoromethane molecules was studied at the Linac Coherent Light Source free-electron laser using an ultraviolet-pump, X-ray-probe scheme. The results for both molecules are discussed with respect to the nature of their UV excitation and different chemical properties. Signatures of long-distance intramolecular charge transfer are observed for both species, and a quantitative analysis of its distance dependence in iodomethane is carried out for charge states up to I21+. The reconstructed critical distances for electron transfer are in good agreement with a classical over-the-barrier model and with an earlier experiment employing a near-infrared pump pulse.